Predictors of Impaired Postpartum Renal Function in Women after Preeclampsia: Results of a Prospective Single Center Study. (31st July 2016) - Kaleta, T.; Stock, A.; Panayotopoulos, D.; Vonend, O.; Niederacher, D.; Neumann, M.; Fehm, T.; Kaisers, W.; Fleisch, M.
Abstract : Objective . The purpose of this prospective study was to investigate the predictive value of single prepartum findings combined with serum biomarkers sFlt-1 (soluble fms-like tyrosine kinase-1) and PlGF (placental growth factor) indicating severity of preeclampsia (PE) for occurrence and extent of impaired postpartum kidney function. Study Design . In this prospective, single center study 44 PE patients were compared to 39 healthy controls (similar in age and gestational age with singleton pregnancy) evaluated at time of delivery and at 6 months and 12 months postpartum.p values below 0.05 are considered statistically significant. Results . The majority of the PE patients had persistence of proteinuria (>120 mg/L after delivery) 6 months (p = 0.02 ) and 12 months postpartum (p < 0.0001 ) compared to controls. Also reduced GFR (glomerular filtration rate) persisted up to 6 months postpartum in PE patients compared to controls (p < 0.001 ). Prepartum sFlt-1 levels indeed correlated with impaired renal function parameters. Conclusion . A significant proportion of our PE patients had lower GFR levels and persistent proteinuria up to 12 months postpartum. Prepartum sFlt-1 is a trend-setting marker for impaired renal function postpartum, but it is not sufficient enough to predict renal impairment after PE. An evaluation of 24-month follow-up data is scheduled.